2020
DOI: 10.7433/s112.2020.08
|View full text |Cite
|
Sign up to set email alerts
|

Branding your identity online! The importance of the family dimension for Italian family wine businesses’ foreign turnover

Abstract: Purpose of the paper: Drawing on the resource-based view and moving from Devigili et al. 's (2018) framework on wine brand identity, the paper aims at investigating which brand identity dimensions family wine businesses are benefiting from in their foreign sales turnover. In particular, it focuses on the impact of the territorial identification (distinguishing between denomination, locality, region and country) and the governance attributes (looking at family, tradition, innovation and storytelling) on foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The research stream on wine brand identity demonstrates high versatility, ranging from interviews to questionnaires to netnographic approaches [62,63]. Some wine brand identity literature relies on standard definitions of brand identity [6], while other authors go on to explore other, wine-specific brand identity variables [64,65]. This research stream has thereby confirmed the importance of places, both as names as well as images, in crafting strong wine brand identity [66,67].…”
Section: Wine Branding: Identity Personality and Imagementioning
confidence: 99%
“…The research stream on wine brand identity demonstrates high versatility, ranging from interviews to questionnaires to netnographic approaches [62,63]. Some wine brand identity literature relies on standard definitions of brand identity [6], while other authors go on to explore other, wine-specific brand identity variables [64,65]. This research stream has thereby confirmed the importance of places, both as names as well as images, in crafting strong wine brand identity [66,67].…”
Section: Wine Branding: Identity Personality and Imagementioning
confidence: 99%
“…The family brand – namely, the “set of associations identified with a particular family” (Parmentier, 2011, p. 218) – can positively affect customers’ perceptions (Blombäck and Brunninge (2016). This is especially true because family history and heritage create a competitive advantage (Gallucci et al , 2015) and market influence for the family wine business (Faraoni et al , 2020). Family wine businesses build on resources, such as the family name, family-owned real estate, and family heritage to develop their identity (Pucci et al , 2017; Rovelli et al , 2022; Vrontis et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are internationally described as ubiquitous (De Massis and Rondi, 2020), impacting entrepreneurial and economic growth (Botero et al , 2018; Maguire et al , 2013). Consequently, South African wineries present a unique and relevant research context (Faraoni et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family businesses are very common in the wine sector, as they possess the tradition of longstanding family companies, as well as unique resources in the form of family name, real estate, heritage and country of origin (Casprini et al, 2020;Faraoni et al, 2020), which are essential elements for building strong brands in the wine industry. However, what are the real values and words used for branding the family SME wineries has still not been documented in the literature.…”
Section: Family and Non-family Sme Winery Branding Inside A Wine Regionmentioning
confidence: 99%